2018
DOI: 10.1103/physrevd.98.054018
|View full text |Cite
|
Sign up to set email alerts
|

Threshold resummation of the rapidity distribution for Drell-Yan production at NNLO+NNLL

Abstract: We consider the production of pairs of lepton through the Drell-Yan process at the LHC and present the most accurate prediction on their rapidity distribution. While the fixed order prediction is already known to next-to-next-to-leading order in perturbative QCD, the resummed contribution coming from threshold region of phase space up to next-to-next-to-leading logarithmic (NNLL) accuracy has been computed in this article. The formalism developed in [1-3] has been used to resum large threshold logarithms in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

7
3

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 82 publications
(138 reference statements)
0
33
0
Order By: Relevance
“…A formalism with applicability to large partonic rapidity, as treated in electroweak annihilation in Ref. [66], will require further development for QCD hard scattering.…”
Section: The Resummed Inclusive Hard-scattering Function In Moment Spacementioning
confidence: 99%
“…A formalism with applicability to large partonic rapidity, as treated in electroweak annihilation in Ref. [66], will require further development for QCD hard scattering.…”
Section: The Resummed Inclusive Hard-scattering Function In Moment Spacementioning
confidence: 99%
“…In perturbative QCD, the fixed order predictions for the observables are often unreliable in certain regions of phase space due to the presence of large logarithms [23]. For example, at the hadron colliders, the inclusive observables like total cross section or invariant mass distribution of finial state colorless state and some differential distributions contain large logarithms which can spoil the reliability of fixed order results.…”
Section: )mentioning
confidence: 99%
“…To achieve this, we exploit the Sudakov (KG) equation that the virtual part (form factor) of the cross section satisfy, renormalization group invariance, factorization theorem and use various three-loop results. We use the framework developed in [16,17,18,19,20] which describes resummation of soft gluons to all orders in QCD perturbation theory. In [17], it was shown that DIS cross section in the threshold limit factorizes into the square of ultraviolet (UV) renormalized form factor, soft plus jet (SJ) function and the mass factorization kernels.…”
Section: Introductionmentioning
confidence: 99%